Measurement Of Solid Matter Methods - et. al., Shertaylaqov G'ayrat Murodovich, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The classification of moisture measurement methods cannot be organized without linking them to liquid or gas moisture measurement methods. Extraction of water from a solid in solution is widely used in physical chemistry. At the end of the extraction, the amount of water in the liquid is measured. Using the principle of evaporation of water in a solid, it is transferred to the gas and the moisture content in the gas is determined. Methods of measuring moisture in solids are divided into methods such as nuclear-physical, optical, physical, electrophysical, physicochemical and extraction-chemical.